TAPI : textiles and art of the people of India (2008)
[Dt.:] Diese Seite präsentiert die TAPI Collection, die aus einigen der schönsten und außergewöhnlichsten historischen Textilien Indiens besteht. Ausgestellt wird die Sammlung in verschiedenen Museen und Galerien innerhalb des Landes. Über vergangene, aktuelle, sowie kommende Ausstellungen wird auf der Homepage informiert . - [Engl.:] The TAPI Textile Collection consists of some of the most exceptional Indian historic textiles. It was brought together from a simple desire to celebrate the richness of the Indian textile tradition and at the same time to serve as a resource bank for design. The collection is hosted by various museums and galleries within India. The homepage informs about previous, current and forthcoming exhibitions.